Department of Avian Diseases, Faculty of Veterinary Medicine, University of Tehran, Tehran, Iran - Nakhaee, Peyman; Mohamad Hafez, Hafez (Journal of Poultry Sciences and Avian Diseases, 2023)
The goal of poultry industry worldwide is the production of safe food products, via eﬃcient and goal-oriented health care to prevent the development of disease conditions in poultry. However, a several number of poultry diseases can negatively affects the breeding values and have the potential to be zoonotic and transmit the infections to humans such as campylobacteriosis. C. jejuni is highly prevalent in commercial poultry farms and act as major reservoirs of the infection. Horizontal transmission from the environment is considered to be the primary source of bacterial foodborne worldwide. The high prevalence of Campylobacter spp. in poultry meat is a result of several contamination and cross-contamination sources in the entire production chain. Recent investigations demonstrated that various stages of food processing in slaughterhouse and consumption of raw or undercooked poultry meat is considered the significant risk factor for human campylobacteriosis worldwide. Furthermore, survival factors such as biofilm formation and antimicrobial resistance, enable its persistence during food processing. On the other hand, the increase of multiple and multidrug-resistant Campylobacter worldwide is not only related to the over-consumption of antibiotics in human medicine, but also in poultry production chain as growth promotors and/or to treat and prevent bacterial infections. Antibiotic resistant Campylobacter presents an obvious and impending challenge to One Health. In the future, the consumer expectations for high standards quality of poultry products will strongly inﬂuence the production methods. This means that farmers, stockholders’, veterinarians, and all other partners involved in the production chain, will have to share more responsibilities and the cooperation should be intensiﬁed. This review represents an updated overview of the global epidemiology, the correlation of official control, the disease associated with food handler and the importance of food safety with respect to Campylobacteriosis.